Characterization of powdered ungurahui (Oenocarpus Bataua) trough freeze-dying processes - Peña Ortiz, Arantza (2025)
The present research develops the characterization of a powdered nutritional supplement from ungurahui (Oenocarpus bataua), a Peruvian Amazon fruit with a high content of antioxidants, unsaturated fatty acids, polyphenols, and tocopherols. Due to its perishability, ungurahui faces barriers to its commercial reach. The research question is: How to preserve the nutritional and sensory properties of ungurahui through freeze-drying to obtain a stable, high-quality supplement? The main objective is to develop and characterize a powdered food product from the ungurahui fruit using the freeze-drying process, in order to obtain a product with a high nutritional (antioxidant) contribution. Methodologically, the study was carried out in the Operations and Unit Processes and Food Laboratories of the University of Lima, following the stages of cleaning, depulping, moisture analysis, blending, freezing, freeze-drying, and packaging. Subsequently, proximal analyses, antioxidant capacity tests (DPPH), polyphenol content, solubility, density, and sensory evaluation were performed. The results showed a moisture reduction in ungurahui from 47.8% to 0.97% and significant retention of antioxidant compounds up to 152.82 mg Trolox/L. The freeze-drying efficiency was 53.3%, and the product obtained positive sensory acceptance, although low solubility between 1% - 3% due to its fiber and fat content. Temperature parameters were optimized at -50°C and drying time at 20 hours to maximize the stability and quality of the freeze-dried ungurahui. The contribution to the valorization of Amazonian fruits through advanced preservation technologies determines that this work is relevant in the functional food industry. The reduction of post-harvest losses and the promotion of functional products of sustainable origin contribute to the importance of fostering learning among young people in this industry.